3
$\begingroup$

In some of the literature (for example, below Eq. (A3) of this paper), the following is claimed to be the Chern-Simons term in the Coulomb gauge: \begin{equation} 2a_0(\partial_1a_2-\partial_2a_1) \end{equation} and it cited this paper, which below its Eq. (5) states that the above term is the Chern-Simons term in radiation gauge.

My questions are:

  1. Is the radiation gauge the same as the Coulomb gauge, where $\partial_1a_1+\partial_2a_2=0$.

  2. Why is the above term the Chern-Simons in the Coulomb gauge? The standard Chern-Simons term is $$\epsilon_{\mu\nu\lambda}a_\mu\partial_\nu a_\lambda=a_0(\partial_1a_2-\partial_2a_1)+a_1(\partial_2a_0-\partial_0a_2)+a_2(\partial_0a_1-\partial_1a_0)$$ After integrating by parts it becomes $$\epsilon_{\mu\nu\lambda}a_\mu\partial_\nu a_\lambda\rightarrow 2a_0(\partial_1a_2-\partial_2a_1)+2a_2\partial_0a_1$$ which still differs from $2a_0(\partial_1a_2-\partial_2a_1)$ by the last term that does not seem to vanish in the Coulomb gauge.

$\endgroup$

1 Answer 1

2
$\begingroup$
  1. Yes.

  2. The question now is to show $$ \int d^2x\epsilon^{\mu\nu\sigma}a_{\mu} \partial_{\mu}a_{\sigma}=\int d^2x [2 a_0(\partial_1 a_2-\partial_2 a_1)+(a_2\partial_0 a_1-a_1\partial_0 a_2)] \\=\int d^2x 2 a_0(\partial_1 a_2-\partial_2 a_1) \tag{1}. $$ That is, $$ \int d^2x (a_2\partial_0 a_1-a_1\partial_0 a_2)=\int d^2x \vec{a}\times \partial_0 \vec{a}=0 \tag{2}. $$ The Coulomb gauge condition ($\nabla \cdot \vec{a}=0$) in momentum space is $\vec{k}\cdot\vec{a}(\vec{k})=0$. Differentiating with respect to time and $k\rightarrow -k$ gives $\vec{k}\cdot \partial_0 \vec{a}(-\vec{k})=0.$. These two equations imply that $\vec{a}(\vec{k})$ and $\partial_0 \vec{a}(-\vec{k})$ are both perpendicular to $\vec{k}$, which in turn imply that they are parallel to each other: $$ \vec{a}(\vec{k}) \times \partial_0 \vec{a}(\vec{-k})=0 \tag{3}. $$ Now, representing (2) in momentum space gives $$ \int d^2x \vec{a}\times \partial_0 \vec{a}=\int \frac{d^2k}{(2\pi)^2}\vec{a}(\vec{k})\times \partial_0 \vec{a}(-\vec k)=0,\tag{4} $$ and the claim is proved.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.